Perancangan Ulang Saringan Vibration Sieve untuk Pengolahan Limbah Padat: Studi Kasus di PT ABC - Enggita, Asadian Puja Enggita; Kurnia, Ganjar; Darmawan, Daffa Athalla (Politeknik Negeri Sriwijaya, Indonesia, 2025)
Effective solid waste management is essential to support industrial operations and environmental sustainability. PT ABC faces obstacles in the solid waste screening due to the less-than-optimal performance of the Vibration Sieve, especially in handling additive-lime and masterbatch-resin. This study aims to evaluate the performance of the tool before and after the redesign of the filter, as well as to determine the appropriate filter specifications for each type of waste. The method used is a quantitative approach through observation, measurement, and performance testing of the tool. The results show that a filter with a hole diameter of 6 mm is effective for additives and lime, while a 3 mm filter is effective for masterbatch and resin. After modification, the weight of the filtered waste increased from 3.26 kg to 16.97 kg. This modification has been shown to increase filtering effectivity and reduce waste